2017
DOI: 10.4103/0028-3886.217947
|View full text |Cite
|
Sign up to set email alerts
|

The influence of initial stroke severity on mortality, overall functional outcome and in-hospital placement at 90 days following acute ischemic stroke: A tertiary hospital stroke register study

Abstract: In this acute stroke cohort, initial stroke severity had a major impact on the likelihood of death following an AIS and appears to be the dominant influence on the overall stroke outcome and in-hospital placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 1 publication
3
26
0
2
Order By: Relevance
“…Our finding is consistent with that of previous reports of a major negative impact of initial stroke severity on the likelihood of death following acute stroke [11]. In this regard, Bhaskar et al [12] observed that initial stroke severity (aOR 1.16; 95%CI 1.12 -1.20) independently predicted mortality following acute ischemic stroke. Similar finding has been also reported by Papagianni et al [13] who found National Institute of Health Stroke Scale (NIHSS) at admission (RR 1.19; 95%CI 1.14 -1.23; p < 0.001) to be one of the main predictors of in-hospital mortality after ischemic stroke.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is consistent with that of previous reports of a major negative impact of initial stroke severity on the likelihood of death following acute stroke [11]. In this regard, Bhaskar et al [12] observed that initial stroke severity (aOR 1.16; 95%CI 1.12 -1.20) independently predicted mortality following acute ischemic stroke. Similar finding has been also reported by Papagianni et al [13] who found National Institute of Health Stroke Scale (NIHSS) at admission (RR 1.19; 95%CI 1.14 -1.23; p < 0.001) to be one of the main predictors of in-hospital mortality after ischemic stroke.…”
Section: Discussionsupporting
confidence: 93%
“…15 Initial NIHSS were also reported as an independent predictor of death after thrombolysis. 16 Subtherapeutic international normalized ratio (INR) in patients using warfarin increases the risk for sICH after thrombolysis. 17 Previous meta-analysis revealed that use of warfarin did not increase mortality in patients received thrombolysis.…”
Section: Journal Of Neurosonology and Neuroimagingmentioning
confidence: 99%
“…Severe stroke can be understood as a stroke resulting in a significant amount of brain tissue damage and multiple neurological impairments, which leads to a significant loss of function and residual disability 12. Dependent on how it is measured, 14%–31% of people who sustain a stroke globally are classified as having a severe stroke,13–18 a cohort of the stroke population that experiences worse outcomes compared with survivors of less severe stroke 19–30. In the initial hospitalisation phase poststroke, they are more likely to develop acute medical complications, which are negatively associated with functional recovery 19.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial hospitalisation phase poststroke, they are more likely to develop acute medical complications, which are negatively associated with functional recovery 19. Three month mortality can be as high as 40%, compared with just under 5% for those patients with mild stroke 20–22. Survivors of severe stroke spend longer in hospital, resulting in increased hospital costs, and demonstrate slower and less functional recovery, resulting in greater dependency when they are discharged from hospital 14 15 23 25.…”
Section: Introductionmentioning
confidence: 99%